Sosialisasi Pemanfaatan Teknologi Elektronik Sebagai Media Pembelajaran Di SD Kertajaya, Pebayuran, Bekasi - Taba, Li Awal; Suryani, Elvira; Rofieq, Ainur (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Technology is a scientific method for achieving practical goals; it is the entire means of providing the goods necessary for the continuity and comfort of human life. Previously, electronic technology was only used as a communication tool, but now the development of electronic technology has been used more to assist teachers in delivering learning. Electronic technology as a medium in learning carried out by teachers greatly facilitates teachers in making media that is more attractive to elementary school students. The colorful displays and animations that are displayed are very diverse to make students more focused on learning. Based on the results of his observations with colleagues from the KKN team in Kertaja Village, Kec. Pebayuran found that one of the problems faced by teachers was the lack of use of electronic technology; teachers methods of conveying learning were limited to books, even though the current development of electronic technology was growing rapidly. Therefore, the more students are presented with various media and supporting infrastructure, the more likely it is that educational values can be absorbed and digested.